The Political Role of Ki Bagus Hadikusumo and Its Relevance as the Development of New Indonesian History Material Source - Ulfiani Mabruroh; Djono Djono; H. Purwanta (Budapest International Research and Critics University, 2022)
The purpose of this study is to describe: (1) the political development during the Indonesian national movement. (2) The political role of Ki Bagus Hadikusumo in 1938-1953. (3) The importance of Ki Bagus Hadikusumo's political role in developing new sources of Indonesian history. The methodology used in this study is historic. The steps of the historical method are enlightenment, criticism, interpretation, and historiography. The data sources used by researchers are primary and secondary sources. Data collection techniques use library search techniques. Data analysis techniques through fact-based external and internal criticism.